206k views
0 votes
Find a unit vector in the same direction as the vector A = 4i−2j+ 4k, and another unit vector in the same direction as B = −4i + 3k. Show that the vector sum of these unit vectors bisects the angle between A and B. Hint: Sketch the rhombus having the two unit vectors as adjacent sides.

2 Answers

5 votes

A unit vector in the same direction as a vector
v can be obtained by multiplying
v by the reciprocal of its norm. So
\vec A and
\vec B have corresponding unit vectors
\vec a and
\vec b,


\vec a=(\vec A)/(\|\vec A\|)=(4\,\vec\imath-2\,\vec\jmath+4\,\vec k)/(√(4^2+(-2)^2+4^2))=\frac23\,\vec\imath-\frac13\,\vec\jmath+\frac23\,\vec k


\vec b=(-4\,\vec\imath+3\,\vec k)/(√((-4)^2+3^2))=-\frac45\,\vec\imath+\frac35\,\vec k

They have vector sum


\vec a+\vec b=-\frac2{15}\,\vec\imath-\frac13\,\vec\jmath+(19)/(15)\,\vec k

Find the angle between
\vec A and
\vec B using the dot product formula:


\vec A\cdot\vec B=\|\vec A\|\|\vec B\|\cos\theta


-4=30\cos\theta


\cos\theta=-\frac2{15}


\theta\approx97.66^\circ

Then find the angle between either
\vec A or
\vec B and
\vec a+\vec b:


\vec A\cdot(\vec a+\vec b)=\|\vec A\|\|\vec a+\vec b\|\cos\varphi


\frac{26}5=2\sqrt{\frac{78}5}\cos\varphi


\cos\varphi=\sqrt{(13)/(30)}


\varphi\approx48.831^\circ

(and this is half of
\theta)

User Vic Nmkf
by
5.4k points
3 votes

Answer with Step-by-step explanation:

We are given that

A=4i-2j+4k

B=-4i+3k


\mid A\mid=√(4^2+(-2)^2+4^2)=6


mid B\mid=√(3^2+(-4)^2)=5


\hat{A}=(A)/(\mid A\mid)


\hat{A}=(4i-2j+4k)/(6)=(2)/(3)i-(1)/(3)j+(2)/(3)k


\hat{B}=(-4i+3k)/(5)=(-4)/(5)i+(3)/(5)k

Sum of unit vectors=
\hat{A}+\hat{B}

Sum of unit vectors=
(2)/(3)i-(1)/(3)j+(2)/(3)k+(-4i+3k)/(5)=(-4)/(5)i+(3)/(5)k

Sum of unit vectors=
(-2)/(15)i-(1)/(3)j+(19)/(15)k


\mid \hat{A}+\hat{B}\mid=\sqrt{((-2)/(15))^2+((1)/(3))^2+((19)/(15))^2}


\mid \hat{A}+\hat{B}\mid=1.32


\theta_1=Cos^(-1)((A\cdot B))/(\mid A\mid \mid B\mid)


\theta_1=cos^(-1)((-4)/(30))=97.6^(\circ)


\theta_2=cos^(-1)(((Sum\;of\;unt\;vectors\cdot A))/(\mid sum\mid \mid A\mid )


\theta_2=cos^(-1)((78)/(15\cdot 2\cdot 1.32\cdot 6))=49^(\circ)


(1)/(2)\theta_1=(1)/(2)(97.6)=48.8\sim 49^(\circ)=\theta_2

Hence, proved.

User Philchalmers
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.